The Effect Of Human Development Index, Minimum Wage, And Open Unemployment Rate On Poverty In East Java Province - Putri, Mitha Rachelia; Fatimah, Atika (Convergence: The Journal of Economic Development, 2024)
ABSTRACT This study aims to analyze the effect of the Human Development Index (HDI), Regency/city Minimum Wage, and Open Unemployment Rate (OUR) on Poverty in East Java Province in 2023. The technique used in this study is multiple linear regression analysis. Based on the results of the analysis, it shows that partially the Human Development Index (HDI) variable has a negative and significant effect on poverty in East Java, while Minimum Wage has a positive and significant effect on poverty in East Java Province. On the other hand, the Open Unemployment Rate does not have a significant effect on poverty in East Java. These findings have important implications for development policy in East Java. Therefore, based on the results of this study, policies that focus on improving human quality through education and health (which support the improvement of the HDI) will be more effective in reducing poverty. Meanwhile, policies related to Regional Minimum Wage need to consider the balance between fair wages and the economic sector's capacity to absorb the workforce. Lastly, although open unemployment is a serious issue, it does not always directly correlate with the poverty rate, as many external factors influence household income. Keywords : Poverty, Human Development Indeks, Minimum Wage, Open Unemployment ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh Indeks Pembangunan Manusia (IPM), Upah Minimum Regency/Kota, dan Tingkat Pengangguran Terbuka (OUR) terhadap Kemiskinan di Provinsi Jawa Timur pada tahun 2023. Teknik yang digunakan dalam penelitian ini adalah analisis regresi linier berganda. Berdasarkan hasil analisis menunjukkan bahwa secara parsial variabel Indeks Pembangunan Manusia (IPM) berpengaruh negatif dan signifikan terhadap kemiskinan di Jawa Timur, sedangkan Upah Minimum Daerah berpengaruh positif dan signifikan terhadap kemiskinan di Provinsi Jawa Timur. Di sisi lain, Tingkat Pengangguran Terbuka tidak berpengaruh signifikan terhadap kemiskinan di Jawa Timur. Oleh karena itu, berdasarkan hasil penelitian ini, kebijakan yang berfokus pada peningkatan kualitas manusia melalui pendidikan dan kesehatan (yang mendukung peningkatan IPM) akan lebih efektif dalam mengurangi kemiskinan. Sementara itu, kebijakan terkait Upah Minimum Daerah perlu mempertimbangkan keseimbangan antara upah yang adil dan kapasitas sektor ekonomi untuk menyerap tenaga kerja. Terakhir, meskipun pengangguran terbuka merupakan masalah yang serius, akan tetapi hal itu tidak selalu berkorelasi langsung dengan tingkat kemiskinan, karena banyak faktor eksternal yang mempengaruhi pendapatan rumah tangga. Kata Kunci : Kemiskinan, Indeks Pembangunan Manusia, Upah Minimum, Tingkat Pengangguran terbuka